2009
DOI: 10.1186/1742-4690-6-4
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic features of the selective pressure on the human immunodeficiency virus type 1 (HIV-1) gp120 CD4-binding site in a group of long term non progressor (LTNP) subjects

Abstract: The characteristics of intra-host human immunodeficiency virus type 1 (HIV-1) env evolution were evaluated in untreated HIV-1-infected subjects with different patterns of disease progression, including 2 normal progressor [NP], and 5 Long term non-progressor [LTNP] patients. Highresolution phylogenetic analysis of the C2-C5 env gene sequences of the replicating HIV-1 was performed in sequential samples collected over a 3-5 year period; overall, 301 HIV-1 genomic RNA sequences were amplified from plasma samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 64 publications
1
17
0
Order By: Relevance
“…Not surprisingly, codons under diversifying selection (positive selection) seem to be clustered mostly in the hypervariable V1/V2 and V3 regions that contain important and accessible neutralizing targets [49], [50]. The impact of the neutralizing antibody response in the in vivo evolution of the HIV-2 Env is currently unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Not surprisingly, codons under diversifying selection (positive selection) seem to be clustered mostly in the hypervariable V1/V2 and V3 regions that contain important and accessible neutralizing targets [49], [50]. The impact of the neutralizing antibody response in the in vivo evolution of the HIV-2 Env is currently unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier, Canducci et al (2009) observed that evolutionary rate of HIV-1 env gene varies between NP and LTNP patients. The evolutionary rate (ω) for the env sequences of RP, SP, and LTNP type was found to correlate significantly with Axis 1 ( R = −0.31, P < 0.01) of RAAU data.…”
Section: Resultsmentioning
confidence: 98%
“…The cocktail strategy may be especially relevant in the case of HIV where cytotoxic T lymphocytes and neutralizing Abs have long been known to select for immune escape mutations during the course of infection [54][55][56][57]. In addition, inactivation of bnAbs by non-nAbs has been reported [58][59][60][61].…”
Section: Introductionmentioning
confidence: 99%